The Utilization of Chicken Fat as Alternative Raw Material for Biodiesel Synthesis - Gugule, S; Fatimah, F; Rampoh, Y (ANIMAL PRODUCTION, 2011)
Abstract. A study of biodiesel production of chicken fat through estrification-transesterification reactions has been conducted. The separation of the chicken fat was conducted using heating technique, while the esterification-transesterification was conducted using ethanol reagent with chloride acid and hydroxide kalium catalyses. The identification results were identified chromatographically and spectroscopically and the chemical properties (peroxide number, acid number and saponification number) were determined. The results of the study showed that the ethyl ester resulting from the chicken fat was dominated by ethyl miristic component (1.25%), ethyl palmitic (22.38%), ethyl palmitoleic (3.35%), ethyl stearic (7.56%), ethyl oleic (45.83%), and ethyl linoleic (17.54%). Moreover, the percentage yield of ethyl ester from es-trans reaction of chicken fat was 66-70 %. The ethyl ester had the same characteristic as biodiesel quality standard.Key Words: chicken fat, esterification, transesterification, biodiesel